Influence of the Quality of Pharmacy Services and Non-Pharmacy on the Decision to Redeem the Prescription and Its Impact on Retreatment of General Outpatient at Pasar Minggu Hospital - Roswita Roswita; Maura Linda Sitanggang; Sahat Saragih (Green Publisher Indonesia, 2024)
The study examines the influence of pharmaceutical and non-pharmaceutical service quality on prescription redemption decisions and subsequent re-treatment decisions among general outpatients at Pasar Minggu Regional Hospital. The hospital has faced challenges, including a decline in outpatient visits and filled prescriptions, affecting its revenue during the 2022-2023 period. Patient perceptions of the pharmacy services significantly impact their decision to return for further medical care. The research aims to assess both direct and indirect effects of service quality on prescription redemption and re-treatment decisions. The study employs a verification approach with a cross-sectional design, using accidental sampling to survey 342 general outpatients between October 2023 and February 2024. Data were analyzed descriptively and inferentially using SEM PLS 3.0, encompassing both outer and inner model analyses through PLS Algorithm, Bootstrapping, and Blindfolding techniques. The findings reveal that the quality of pharmaceutical and non-pharmaceutical services significantly influences the decision to redeem a prescription (P = 0.000). Moreover, non-pharmaceutical service quality and the decision to redeem a prescription significantly affect the decision to re-medicate (P = 0.002 and 0.000, respectively). However, pharmaceutical service quality alone does not positively impact repeat treatment (P = 0.041). Both service variables have a significant indirect effect on re-treatment decisions through the mediating role of prescription redemption (P = 0.000).